A test to assess aerobic and anaerobic parameters during maximal exercise in young girls - McGawley, K.; Leclair, E.; Dekerle, J.; Carter, H.; Williams, C. A. (Pediatric Exercise Science, 2012)
The Wingate cycle test (WAnT) is a 30-s test commonly used to estimate anaerobic work capacity (AWC). However, the test may be too short to fully deplete anaerobic energy reserves. We hypothesized that a 90-s all-out isokinetic test (ISO_90) would be valid to assess both aerobic and anaerobic capacities in young females. Eight girls (11.9 ± 0.5 y) performed an exhaustive incremental test, a WAnT and an ISO_90. Peak VO2 attained during the ISO_90 was significantly greater than VO2peak. Mean power, end power, fatigue index, total work done and AWC were not significantly different between the WAnT and after 30 s of the 90-s test (i.e., ISO_30). However, 95% limits of agreement showed large variations between the two tests when comparing all anaerobic parameters. It is concluded that an ISO-90 may be a useful test to assess aerobic capacity in young girls. However, since the anaerobic parameters derived from the ISO_30 did not agree with those derived from a traditional WAnT, the validity of using an ISO_90 to assess anaerobic performance and capacity within this population group remains unconfirmed.